Assessing the Effects of LULC Change on Landslide Hazards in Rwanda: A Case Study in Nyabihu District - Hafashimana, Nathanael; Sebego, Reuben Jack; Kenabatho, Piet Kebuang; Lekoko, Rebecca Nthogo; Maphanyane, Joyce Gosata (Journal of Environmental Geography, 2022)
Landslides have become important environmental hazard in hilly regions of Rwanda such as Nyabihu district. They are characterized by the downslope movement of debris or other earth materials which damage or destroy everything found in their way such as infrastructure, croplands, and even cause a number of human deaths. The main triggering factors of landslides in Rwanda are intense rainfall and land use/land cover (LULC) change. Therefore, the objective of this study was to assess the LULC change effects on landslide occurrences. LULC maps of 2005 and 2015 were generated and overlaid with mapped landslides. Maximum likelihood classification was used to classify the Landsat satellite images. The results revealed a remarkable decrease of agricultural land, while all other LULC types have increased in the studied period. It was noted that most of the landslides occurred in agricultural land. The study results are expected to be useful for landslide hazard management decisions, land use planning and management regulations, so as to minimize the likelihood of landslide occurrences and their resultant impacts.